REFLECTION ON TECHNICAL EDUCATION IN A GLOBALIZING WORLD - SERAFIN, Cestmir (Trends in education, 2014)
Globalization is a phenomenon of our time, which has a dimension of social, political, economic and social. In today's world that occurs as a result of close but at the same time a growing interconnectedness between the entities to change, which must inevitably occur in the operation of the company and also, or mainly, in educational systems.
Keywords: Globalization; education; technical education; teacher training.